Modified dual osteotomy for Madelung’s deformity - Agarwal, Aditya; Patel, Rahul; Jain, Mohit; Arora, Shubham; Golwala, Paresh; Agarwal, Srishty (International Journal of Research in Orthopaedics, 2023)
Madelung’s deformity is one of the rare congenital deformities of the forearm and wrist, typically seen as positive ulnar variance and increased volar tilt due to the “Vickers” ligament. Different corrective surgical methods for this have been done in the literature. In this case of a 9-year-old Madelung’s like deformity, we have performed a modified dual osteotomy with periosteal preservation allowing natural articulation and bone to be modified, especially in a younger child. This article gives the surgical option to orthopedics for the future, especially in a younger child with severe deformity. This is a level V evidence-based therapeutic study.